The impact of comprehensive tobacco control policies on cardiovascular diseases in Beijing, China. (28th January 2021) - Wu, Yiqun; Wang, Zijing; Zheng, Yunting; Wang, Mengying; Wang, Siyue; Wang, Jiating; Wu, Junhui; Wu, Tao; Chang, Chun; Hu, Yonghua
Abstract: Background and Aims: China has a high smoking prevalence, but lacks effective tobacco control interventions. In 2015, comprehensive policies that incorporated all six aspects of MPOWER were implemented in Beijing and were considered the strictest tobacco control policy implemented in China to date. Decreases in the prevalence of active smoking and secondhand smoke (SHS) exposure were observed thereafter. This study aimed to evaluate the impact of Beijing's 2015 tobacco control policy package on cardiovascular diseases (CVDs). Design: Interrupted time–series study. Setting: Beijing, China. Participants: A total of 17.7 million employees enrolled in Urban Employee Basic Medical Insurance (UEBMI) between January 2013 to June 2017. Interventions: Beijing's 2015 comprehensive tobacco policy package, combining a complete ban on smoking in indoor public places, cessation support, more comprehensive bans on advertising, and tax rises. Measurements: The main outcome was hospital admissions for all CVDs and five major cause‐specific CVDs, including ischaemic heart disease (IHD), heart failure (HF), heart rhythm disturbances (HRDs), stroke and other cerebrovascular diseases (CBDs). The absolute number and proportion of reductions in the number of hospital admissions after the policies are reported. Findings: A total of 419 875 hospital admissions for CVD were identified. In total, 13.4% [95% confidence interval (CI) = 11.5%, 15.3%] of hospital admissions for CVD were averted by the tobacco control policies. For major cause‐specific CVDs, significant hospital admission reductions occurred for IHD (5.4%, 95% CI = 2.6%, 8.3%), stroke (21.2%, 95% CI = 17.8%, 24.6%) and other CBDs (25.9%, 95% CI = 20.8%, 31.0%), but not for HF (4.7%, 95% CI = −4.2%, 13.5%) or HRDs (4.7%, 95% CI = −2.9%, 12.3%). Conclusions: Beijing's 2015 tobacco control policy package appears to have been associated with a more than 10% reduction in all cardiovascular hospital admissions, including a more than 20% reduction in admissions for cerebrovascular diseases.